Refugee farmer development at Juniper Gardens Training Farm - Semra Fetahovic (Urban Food Systems Symposium, 2020)
The Juniper Gardens Training Farm is a partnership between Cultivate KC, Catholic Charities of Northeast Kansas and the Kansas City, KS Housing Authority. The farm is in northeast Kansas City, KS in the middle of Kansas’ oldest and largest public housing project. In 2020 the 9-acre site was home to a dozen community gardeners, 15 farm families in training, and three program graduates who lease plots and farm infrastructure for the growing season. The four-year farm incubation program (New Roots for Refugees), started in 2008, assists re-settled refugees in starting independent farm businesses on ¼ acre plots and provides four years of production, marketing, and business management skills through farm classes and one-on-one training from trained staff. As of 2019 we have graduated 32 farm families from the program, and over 80% of them are still growing and selling in the Kansas City Metro. Farmers in the program come from extremely different backgrounds, with varying levels of education, language and farming skills; thus, program training must remain dynamic to meet both farmer needs and the ever-changing agricultural environment they are growing in. We will present on our educational model, which has been developed to suit our refugee farmers, but can also be adapted to other non-English speakers and audiences with different educational levels. Training at Juniper Gardens starts in the winter with English classes, transitions into the spring with production planning and farm classes, and continues throughout the growing season with one-on-one field walks. Program funding is scaffolded in that trainees receive more financial assistance in the first year and this slowly decreases during their time in the program, so that by the fourth year they are prepared to incur these expenses once they are on their own. In the past year, more efforts have been made to scaffold the educational components of the program as well. English classes are offered at different levels based on skill level, frequency of field walks is based on years in the program and farmer preference, and farm classes vary in content based on skill and years in the program. One of the largest challenges is synchronizing all of the materials and data collection across different teaching methods (i.e., field walks, English classes, and farm classes). Throughout the years, our teaching methods have been altered and adapted, this presentation will focus on current best practices, but will also reflect on challenges and adaptation needs.